Development and Deployment of an IoT-Based Telemedicine System for Infant Warming Devices - Fauzi, Ekha Rifki; Doungjan, Kamonthip; Respati, Hanif Budi (Universitas Nurul Jadid, 2025)
Neonatal hypothermia is a serious health concern, especially for premature babies and those with low birth weight, often resulting in complications like metabolic acidosis, hypoxia, and an increased risk of other health issues. To address this, newborn warming technologies have been developed, offering a controlled environment to regulate the baby’s body temperature. This study focuses on creating and implementing an IoT-powered telemedicine system that works with an infant warming device to enhance neonatal care. The system includes sensors to monitor temperature and heart rate in real time, ensuring the baby's safety and promoting the best possible clinical outcomes. With IoT architecture, healthcare professionals can remotely manage and monitor the baby's condition, making quick decisions when necessary. This approach overcomes the limitations of current devices by incorporating fuzzy logic control alongside real-time telemedicine features, all accessible via portable devices. By integrating these technologies, the system offers a solution to managing neonatal hypothermia, especially in settings with limited resources. Additionally, it has the potential to cut down on hospital transfers, improve outcomes for newborns, and ease the burden on caregivers and families. The research suggests that this IoT-enabled infant warming system could significantly boost the effectiveness of neonatal care, making it an invaluable tool for healthcare professionals.